Disability studies after the ontological turn: a return to the material world and material bodies without a return to essentialism - Feely, Michael (Disability & Society, 2016)
Over recent decades, poststructuralist theories have allowed critical disability scholars to challenge essentialist understandings of the human species and to contest discourses which divide humans into ‘normal’/‘impaired’ subjects with respect to a wide – and ever expanding – range of corporeal and cognitive traits. For critics, however, these theories are deeply flawed. By focusing primarily on language, poststructuralism shifts our critical attention away from the often harsh material realities of life for disabled people. This has led some to turn to critical realism and to effectively re-essentialise impairment. In this article, I wish to consider an alternative approach. I suggest that the recent ‘ontological turn’ in social theory has seen the emergence of new-materialist approaches – including Deleuze and Guattari’s ontology of assemblage and methodology of assemblage analysis – which allow us to consider disability as a material phenomenon without a return to essentialism.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; corps; cours; discipline; féminisme matérialiste; histoire et politique; humaines; ontologie; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; thématiques; études critiques du handicap

L’économie politique du sexe : transactions sur les femmes et systèmes de sexe/genre - Rubin, Gayle (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 1998)
La littérature sur les femmes — tant féministe qu’antiféministe — est une longue rumination quant à la nature et à la genèse de leur oppression et de leur subordination sociale. La question n’est pas sans importance, car les réponses qui lui sont données déterminent la manière dont nous envisageons l’avenir et si nous jugeons réaliste ou non d’espérer une société égalitaire entre les sexes. Plus important, l’analyse des causes de l’oppression des femmes fonde toute estimation de ce qu’il faudrait exactement changer pour réaliser une société sans hiérarchie de genre
Keywords: 1900-1999; 1960-1969; 1970-1979; anthropologie; approches et analyses; capitalisme; classe ouvrière; cours; discipline; europe; famille; fem1000; france; féminisme matérialiste; histoire et politique; inégalités; marxisme; patriarcat; premier cycle; psychanalyse; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences; sciences humaines; soc1016; soc2014; sociologie; systèmes d'oppressions; thématiques; théories féministes

Identité sexuelle/sexuée/de sexe? Trois modes de conceptualisation du rapport entre sexe et genre - Mathieu, Nicole-Claude (Catégorisation de sexe et constructions scientifiques, 1989)
Keywords: approches et analyses; corps; cours; discipline; discours dominant; essentialisation; féminisme matérialiste; genre; histoire et politique; identité sexuelle; identités; naturalisation; philosophie politique; premier cycle; sciences; sciences humaines; sex3383; sexe; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; épistémologies féministes